Step forward : - Adelson-Goldstein, Jayme (Oxford University Press, 2007)
The Step-by-Step Lesson Plans provide strategies for conducting Student Book activities and applying the lesson to the multilevel classroom. It offers interleaved student book pages, detailed lesson plans with multilevel teaching strategies and tips, and a CD-ROM of printable multilevel grammar practice.